2022
DOI: 10.3389/fcimb.2022.860559
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Anti-Adenovirus Mechanism of Sargassum fusiforme

Abstract: Human adenovirus (HAdV) has a worldwide distribution and remains a major pathogen that leads to infections of the respiratory tract. No specific treatments or vaccines are yet available for HAdV infection. Sargassum fusiforme, an edible seaweed, has attracted a lot of attention for its various bioactivities. S. fusiforme has been reported to exhibit antiviral activity. However, research studies about its anti-HAdV activity are few. In this research, we found that S. fusiforme had low cytotoxicity and possessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…136 Feng et al found that the extract of S. f usiforme has antivirus potential on human adenovirus-7 (HADV-7), and the most effective component is alginate. 137 In addition, they found that the phase in which the adenovirus reacted with alginate after it was added was the most effective phase for antiviral, and its antivirus effect may related to the endoplasmic reticulum stress (ERS) pathway. 137 Sun et al proved that low molecular weight S. f usiforme polysaccharide has antivirus activity against avian leukosis virus-J (ALV-J), but this function is only effective in the virus adsorption phase.…”
Section: Antivirus and Antibacterial Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…136 Feng et al found that the extract of S. f usiforme has antivirus potential on human adenovirus-7 (HADV-7), and the most effective component is alginate. 137 In addition, they found that the phase in which the adenovirus reacted with alginate after it was added was the most effective phase for antiviral, and its antivirus effect may related to the endoplasmic reticulum stress (ERS) pathway. 137 Sun et al proved that low molecular weight S. f usiforme polysaccharide has antivirus activity against avian leukosis virus-J (ALV-J), but this function is only effective in the virus adsorption phase.…”
Section: Antivirus and Antibacterial Activitiesmentioning
confidence: 99%
“…137 In addition, they found that the phase in which the adenovirus reacted with alginate after it was added was the most effective phase for antiviral, and its antivirus effect may related to the endoplasmic reticulum stress (ERS) pathway. 137 Sun et al proved that low molecular weight S. f usiforme polysaccharide has antivirus activity against avian leukosis virus-J (ALV-J), but this function is only effective in the virus adsorption phase. To make the antiviral activity of SFP better, they prepared three new S. f usiforme polysaccharide long-chain alkyl nanomicelles (SFP-C12M, SFP-C14M, and SFP-C16M).…”
Section: Antivirus and Antibacterial Activitiesmentioning
confidence: 99%
See 1 more Smart Citation